Front Cover: Stearidonic‐Enriched Soybean Oil Modulates Obesity, Glucose Metabolism, and Fatty Acid Profiles Independently of Akkermansia muciniphila. Issue 17 (4th September 2020) - Segura Munoz, Rafael R.; Quach, Truyen; Gomes‐Neto, João C.; Xian, Yibo; Pena, Pamela A.; Weier, Steven; Pellizzon, Michael A.; Kittana, Hatem; Cody, Liz A.; Geis, Abby L.; Heck, Kari; Schmaltz, Robert J.; et al.
Abstract : Mol. Nutr. Food Res . 2020, 64, 2000162 DOI: 10.1002/mnfr.202000162 Utilizing germ‐free mice colonized with complex gut microbiomes devoid of Akkermansia muciniphila, Segura Munoz and colleagues found that feeding transgenic soybean oil enriched in n‐3 PUFA reduced fat deposition, improved glucose metabolism, and increased tissue n‐3 PUFAs independently of A. muciniphila . However, A. muciniphila modulated saturated and mono‐unsaturated fatty acid levels in host adipose tissues. This is reported in article 2000162 .